PRACTICAL APPLICATION OF MULTIMEDIA TECHNOLOGIES IN TEACHING COMPUTER ORIENTATION FOR ENGINEERS- PEDAGOGUES SEWING PROFILE - Seydametova, З.Н. (Journal of Information Technologies in Education (ITE), 2011)
In the article possibilities of practical application of multimedia technologies are considered in an educational process on the example of discipline of computer orientation of engineers- pedagogues of sewing type is the «Computer constructing of clothes».